Current status and perspectives of xanthones production using cultured plant biocatalyst models aided by in-silico tools for its optimization. (2nd April 2020) - Khattab, Amira R.; Farag, Mohamed A.
Abstract: With an increasing interest in exploring the biocatalyst potential for the production of natural products (NP), research in NP biotechnology now follows. Xanthones constitute an important class of phytochemicals exhibiting a myriad of bioactivities and potential for interacting with multimolecular targets, and xanthones are considered to be privileged phytochemical scaffolds in medicinal chemistry. Recent advances in xanthones biosynthetic pathways are outlined and their metabolic engineering. This review summarizes the state-of-the-art processes for the biotechnological production of xanthones, its limitations, and potential improvements. The in vitro tissue culturing methods employed for the production of xanthones from different species of plant are reviewed addressing differences in xanthone classes. This review sheds the light of computational approaches, viz., response surface methodology (RSM) and artificial neural networks (ANN), for optimizing the culture performance and improving xanthones production.